Vascular Aging across the Menopause Transition in Healthy Women. (17th July 2014) - Moreau, Kerrie L.; Hildreth, Kerry L.
Abstract : Vascular aging, featuring endothelial dysfunction and large artery stiffening, is a major risk factor for developing cardiovascular disease (CVD). In women, vascular aging appears to be accelerated during the menopause transition, particularly around the late perimenopausal period, presumably related to declines in ovarian function and estrogen levels. The mechanisms underlying endothelial dysfunction and large artery stiffening with the menopause transition are not completely understood. Oxidative stress and the proinflammatory cytokine tumor necrosis factor- α contribute to endothelial dysfunction and large artery stiffening in estrogen-deficient postmenopausal women. Habitual endurance exercise attenuates the age-related increase in large artery stiffness in estrogen-deficient postmenopausal women and can reverse arterial stiffening to premenopausal levels in estrogen-replete postmenopausal women. In contrast, estrogen status appears to play a key permissive role in the adaptive response of the endothelium to habitual endurance exercise in that endothelial improvements are absent in estrogen-deficient women but present in estrogen-replete women. We review here the current state of knowledge on the biological defects underlying vascular aging across the menopause transition, with particular focus on potential mechanisms, the role of habitual exercise in preserving vascular health, and key areas for future research.